Covid-19 Handling Policy in Cibalongsari Village, Klari District, Karawang Regency - Eva Apriliani Rukmana; Rachmat Ramdani; Lukmanul Hakim; Evi Priyanti (Peneliti.net, 2022)
To achieve the success and sustainability of development programs, community participation is an important aspect. Because participation is the participation of a person or group of people in an activity that is carried out consciously. The sustainability of the results of development and development itself will not succeed if it is not supported by the participation of the community. In an empowerment program, community participation must cover the entire process from the initial stage to the final stage. Slamet (2003:8) states that Valderama's participation in Arsito notes that there are three traditions of the concept of participation, especially when it is associated with the development of a democratic society, namely 1). Political participation 2). Social participation (social participation) 3). Citizen participation (citizen participation/citizenship). This concept has the meaning under the community and also the government or any party can be involved in the implementation of policies so that it can be easier to achieve the desired goals, especially in this concept the power and influence of the community has a big role in the success of a policy. The attitude of the community is very important in providing participation in development programs, although there are several possible responses in the field. In principle, every empowerment carried out by the community must always be improved in quality according to the wishes of the client (community) under it, but in reality this is not the case. One way to improve the quality of empowerment is to fulfill public complaints.